2001
DOI: 10.1071/ar01067
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of markers in Australian wheat breeding

Abstract: Genetic associations of morphological, biochemical, and DNA markers with economically important traits can be used for indirect selection of the traits. Chromosomal linkage between pseudo-black chaff and the stemrust resistance gene Sr2, and between the red glume gene (Rg1) and the stripe rust resistance gene Yr10, have been used in this way for many years. Similarly, linkages between disease resistance genes, such as Sr38,Lr37, and Yr17, have been used to achieve resistance to multiple diseases while selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(49 citation statements)
references
References 0 publications
1
47
0
1
Order By: Relevance
“…Gleanlea (GluA3g), Cloutier et al (2001) have reported positive effects for the Glu-A3 locus on dough strength. In Australia, specific LMW-GS alleles have been actively selected against is certain breeding programs, for example Glu-B3e (Lawrence 1986) and GluA3e (Eagles et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Gleanlea (GluA3g), Cloutier et al (2001) have reported positive effects for the Glu-A3 locus on dough strength. In Australia, specific LMW-GS alleles have been actively selected against is certain breeding programs, for example Glu-B3e (Lawrence 1986) and GluA3e (Eagles et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Classical examples of traits that are difficult and laborious to measure are cereal cyst nematode and root lesion nematode resistance in wheat (Eastwood et al 1991;Eagles et al 2001;Zwart et al 2004 These advantages can be exploited by breeders to accelerate the breeding process (Ribaut & Hoisington 1998;Morris et al 2003). Target genotypes can be more effectively selected, which may enable certain traits to be 'fast-tracked', resulting in quicker line development and variety release.…”
Section: Overview Of Dna Markers Qtl Mapping and Marker-assisted Sementioning
confidence: 99%
“…), and root lesion nematode (Pratylenchus spp.) resistance in wheat are examples of traits that are difficult to evaluate (Buerstmayr et al 2009;Miedaner and Korzun 2012;Eastwood et al 1991;Eagles et al 2001;Zwart et al 2004). Secondly, MAS allows for pyramiding of multiple genes by screening multiple markers on individual plants of a population, thereby greatly expediting the production of breeding lines.…”
Section: Discussionmentioning
confidence: 99%